Slave trading records from William Davenport & Co., 1745-1797. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2009)
William Davenport was a Liverpool merchant and British slave trader. From the late 1740s till the early 1790s, he invested regularly in the African slave trade and was a partner in slaving ventures with other leading merchant Liverpool families. These papers from Keele University Library are accompanied by an online guide to the collection by Professor David Richardson, Hull University.
Date range: 1745-1797.
Keywords: Save trade -- England -- Liberpool -- History -- 18th century